A neoplasm associated with the meninges of the spinal canal – a case report - Kulczyński, Marcin; Sapko, Klaudia; Marciniec, Michał; Caban, Kinga (Journal of Education, Health and Sport, 2019)
Introduction: Spinal canal neoplasms are a heterogeneous group of diseases including both primary and metastatic tumors, either benign or malignant. These tumors can develop both intraspinally and peripherally. Spinal canal tumors are four times less frequent than intracranial tumors. Four-limb paresis may be one of the leading symptoms of a spinal canal tumor. Case report: A 76-year-old female patient was admitted to Neurology Dept. Due to progresive paresis of the lower limbs, muscle weakness, gait disorders and urinary incontinence. A spine MRI revealed a contrast enhancement of the meninges of the spinal cord over the entire length of the spinal cord in the sections covered by the MRI, as well as numerous focal lesions associated with the meninges, which were most likely cancer metastatic foci. CT of the chest, abdominal cavity and pelvis showed no signs of primary neoplasm. A PET scan was scheduled for a patient, but it was abandoned due to haemorrhagic incydent within the brain of the patient. Head MRI revealed no signs of primary cancer focus as well. Histopathological examination of the CSF revealed no specific changes. The patient died, and the autopsy was not performed accordingly to family’s request. Discussion: Cancers of unknown primary origin constitute 3-5% of all cancer cases. These, usually fast-progressing cancers are a huge diagnostic difficulty, which results in mediocre effects of treatment of patients who already have cancer metastases, but it is not known what type of cancer doctors are dealing with. In approximately 20% of patients with cancer with an unknown origin, the primary tumor cannot be determined despite the specialized examinations. In such cases, often only post-mortem examination gives a chance to make the correct diagnosis.